Optimizing Exercise for the Prevention and Treatment of Type 2 Diabetes - Kristian Karstoft (Frontiers Research Topics, 2018)
This eBook contains a collection of peer-reviewed original and review articles published in either Frontiers in Endocrinology or Frontiers in Physiology focused on the research topic Optimizing Exercise for the Prevention and Treatment of Type 2 Diabetes.